PENERAPAN STRATEGI BELAJAR AKTIF TIPE GIVING QUESTION AND GETTING ANSWER DISERTAI KUIS DALAM PEMBELAJARAN MATEMATIKA SISWA KELAS VIII SMPN 1 PANCUNG SOAL TAHUN PELAJARAN 2012/2013 - Nengsih, Diana Ferdina; Mukhni, Mukhni; Haryono, Yulia (Pendidikan Matematika, 2013)
The research was background by the result of the studentsâ value is low, studentsâ activity is not effective and the students afraid to extend their idea and their opinion about lesson material that just was learned. The research has purpose to know: 1. how students learning activity in mathematics subject by apply active learning method type Giving Question and Getting Answer faith Quiz at grade VIII students of SMPN 1 Pancung Soal. 2. does the score mathematics that apply active learning method type Giving Question and Getting Answer faith Quiz be better than conventional method. Kind of the research is experimental research. To take the sample by using random sample, VIII.2 as experimental class and VIII.3 as control class. Can conclude that the score of studentsâ mathematics subject by using active learning type Giving Question and Getting Answer faith Quiz be better than the score of learning that apply conventional method.